Lysomotropic amines cause intracellular accumulation of receptors for epidermal growth factor. - King, A C (1980)
By direct biochemical methods, we demonstrate that the process of internalization of receptors for epidermal growth factor (EGF) occurs even without EGF stimulation and is not prevented by the lysomotopic agents methylamine or chloroquine. These agents inhibit the degradation of 125I-labeled EGF, thus preventing the rapid dissociation of EGF from cells. Furthermore, 125I-labeled EGF incubated with cells in the presence of methylamine becomes increasingly insensitive to trypsin with time, suggesting that the EGF receptor internalization is not prevented by alkylamines, but that there is an intracellular accumulation of ligand--receptor complex due to the loss of normal modes of ligand-induced receptor processing. Lysis of cells treated with methylamine results in recovery of 125I-labeled EGF binding. Fractionation of these lysates on sucrose density gradients demonstrates that EGF receptors are localized within membrane fractions having higher densities than fractions from lysates of untreated cells.